Ethical Approach in Blended Learning Teaching Skills in Macroeconomic Theory Courses - Muslim, Fachruddiansyah; Mayasari; Setyonegoro, Agus; Putra, Wahyu; Sofyan (Eduscape : Journal of Education Insight, 2025)
Blended learning, which combines face-to-face and online learning, has become widely adopted in higher education to enhance flexibility and accessibility for students. However, challenges in interactive communication remain, particularly in complex subjects like Macroeconomics Theory at FKIP Universitas Jambi. This study explores the implementation of ethical approaches in teaching skills within blended learning environments. Utilizing a quantitative research method, data were collected through a survey of 200 students. The results indicate significant challenges in interactive communication, with 80% of students reporting difficulties, yet overall satisfaction and learning outcomes were high. This finding underscores the importance of integrating ethical principles in digital teaching to improve interaction quality and student understanding. Conclusions highlight the necessity of ongoing support for students and lecturers in ethical digital communication. Future research should consider longitudinal studies and qualitative approaches to provide deeper insights into the long-term effects and experiences of blended learning.